Acute Toxicity of Household-Scale Lebak Batik Industrial Wastewater on Common Carp - Oktavia, Swastika; Novi, Cory (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2021)
The concentration of Lebak Batik industrial wastewater contains the pollutant element of lead metal that negatively impacts organisms' content in the water. This study was focused on the acute toxicity of household-scale Lebak Batik industrial wastewater on carp. The methods used were waste characteristics test, animal acclimatization, acute toxicity test for 96 hours with 0, 10, 20, 30, 40, and 50% treatments, measurement of environmental parameters, and data analysis using probit analysis. The results showed that the lethal time (LT50) and lethal concentration (LC50) for 96 hours of treatment were 1,8 days and 8,56%, respectively, with a Toxicity Unit Area (TUa) of 11,68. This proved that the wastewater from the Lebak batik industry had a major effect on causing acute toxicity.